Insights into the Role of Commensal-Specific T Cells in Intestinal Inflammation - Gehlhaar A; Inala A; Llivichuzhca-Loja D; Silva TN; Adegboye CY; O'Connell AE; Konnikova L (Dove Medical Press, 2022)
Arne Gehlhaar,1,* Ashwin Inala,1,* Dhana Llivichuzhca-Loja,1,* Tatiana N Silva,1,* Comfort Y Adegboye,2 Amy E O'Connell,2,3 Liza Konnikova1,4,5 1Department of Pediatrics, Yale University, New Haven, CT, USA; 2Division of Newborn Medicine, Boston Children's Hospital, Boston, MA, USA; 3Department of Pediatrics, Harvard Medical School, Boston, MA, USA; 4Department of Obstetrics, Gynecology and Reproductive Sciences, Yale University, New Haven, CT, USA; 5Program in Human and Translational Immunology, Yale University, New Haven, CT, USA*These authors contributed equally to this workCorrespondence: Amy E O'Connell, Division of Newborn Medicine, Boston Children's Hospital, 300 Longwood Ave, Boston, MA, USA, Tel +1 617 919-2358, Email amy.oconnell@childrens.harvard.edu Liza Konnikova, Department of Pediatrics, Yale University, 375 Congress Ave, LSOG 405B, New Haven, CT, USA, Tel +1 203 737-8016, Email liza.konnikova@yale.eduAbstract: Trillions of microorganisms exist in the human intestine as commensals and contribute to homeostasis through their interactions with the immune system. In this review, we use previous evidence from published papers to elucidate the involvement of commensal-specific T cells (CSTCs) in regulating intestinal inflammatory responses. CSTCs are generated centrally in the thymus or peripherally at mucosal interfaces and present as CD4+ or CD8+ T cells. Bacteria, fungi, and even viruses act commensally with humans, warranting consideration of CSTCs in this critical relationship. Dysregulation of this immunological balance can result in both intestinal inflammation or damaging autoimmune responses elsewhere in the body. Given the relative novelty of CSTCs in the literature, we aim to introduce the importance of their role in maintaining immune homeostasis at barrier sites such as the intestine.Keywords: commensal, T cells, immunity, microbiome